2003
DOI: 10.1021/ol035849+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the C-1−C-28 ABCD Unit of Spongistatin 1

Abstract: The synthesis of the C-1-C-28 ABCD fragment of spongistatin is described. Anti-selective boron-mediated aldol coupling of a CD spiroketal ketone fragment to an AB spiroketal aldehyde unit forms the desired C1-C28 advanced intermediate. Other features include the double conjugate addition of a dithiol to an ynone to generate the key beta-keto-dithiane unit required for the synthesis of the AB spiroketal fragment. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 11 publications
(16 reference statements)
0
58
0
4
Order By: Relevance
“…This technique, first introduced by Ley et al in 2001 (see Section 2.9.4), [51] is becoming increasingly popular, as demonstrated by the many recently published examples. [52][53][54][55][56][57][58][59][60] Systematic studies on temperature profiles and the thermal stability of ionic liquids under microwave irradiation conditions by Leadbeater and Torenius [52,53] have shown that addition of a small amount of an ionic liquid (0.1 mmol mL À1 solvent) suffices to obtain dramatic changes in the heating profiles by changing the overall dielectric properties (namely, tand) of the reaction medium.…”
Section: Heck Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique, first introduced by Ley et al in 2001 (see Section 2.9.4), [51] is becoming increasingly popular, as demonstrated by the many recently published examples. [52][53][54][55][56][57][58][59][60] Systematic studies on temperature profiles and the thermal stability of ionic liquids under microwave irradiation conditions by Leadbeater and Torenius [52,53] have shown that addition of a small amount of an ionic liquid (0.1 mmol mL À1 solvent) suffices to obtain dramatic changes in the heating profiles by changing the overall dielectric properties (namely, tand) of the reaction medium.…”
Section: Heck Reactionsmentioning
confidence: 99%
“…[137] Here it was essential to use openvessel technology, since the two equivalents of the volatile byproduct ethanol that formed under normal (atmospheric pressure) conditions were simply distilled off and therefore Scheme 19. Petasis olefination, [60] hydrosilylation of ketones, [134] and Dötz benzannulation. [135] CAN = cerium ammonium nitrate, TBS = tertbutyldimethylsilyl, TES = triethylsilyl, TIPS = triisopropylsilyl.…”
Section: Heterocycle Synthesismentioning
confidence: 99%
“…Their basic mono-or bis-spiroketal framework resembles that found in many relevant natural products, including steroidal saponins, polyether ionophores, macrolide antibiotics, insect pheromones, and toxic metabolites from algae and fungi [1][2][3][4][5], and is the target of much synthetic effort [6][7][8][9][10][11][12][13][14]. DFAs are formed upon thermal and/or acidic activation of sucrose-and/or D-fructose-rich materials.…”
Section: Introductionmentioning
confidence: 99%
“…Die Synthese von Fragment 4 startete mit einer WittigOlefinierung von Aldehyd 6 [11,12] und dem Entschützen im Sauren. [13] Der Alkohol 10 wurde mit Dess-Martin-Periodinan oxidiert und durch Wittig-Reaktion mit dem stabilisierten Ylid 11 zum Ester 12 olefiniert (Schema 3).…”
unclassified